Haze-protective self-care behaviours in Sarawak, Malaysia: a state-representative cross-sectional study - Sam Froze, Jiee; Lim, Jyh Hann; Lim, Siong Hee; Romano, Ngui; Timothy Adrian, Jinam; Neilson Richard, Seling; Anselm, Su Ting; Jeffery, Stephen (Springer Nature Limited, 2026)
Transboundary haze is a recurrent hazard in Borneo that elevates particulate exposure to health-relevant levels. We conducted a community-based cross-sectional survey of adults across Sarawak, Malaysia, using multistage sampling (n = 481) to assess haze-related protective self-care behaviours during haze. The primary outcome was a Likert-based self-care index categorised into Poor/Moderate/Good using sample quartiles. Determinants included haze tolerance score (as operationalised in this study), political trust, perceived costs, haze knowledge, and community resilience, alongside sociodemographic and access indicators. Analyses included zonal comparisons and proportional odds regression with sensitivity analyses using multinomial regression and the continuous self-care score. Only 25.6% achieved good self-care, while 49.3% were moderate; self-care differed by zone, with the Northern zone scoring highest despite lower trust/knowledge profiles. In adjusted ordinal models, proximity to a health facility was associated with a higher self-care category (OR 3.38, 95% CI 2.17–5.27; p < 0.001), while unmarried status was associated with a lower category (OR 0.48, 95% CI 0.28–0.82; p = 0.007). Higher tolerance score (OR 1.18, 95% CI 1.09–1.28; p < 0.001) and haze knowledge (OR 1.18, 95% CI 1.07–1.30; p = 0.001) were positively associated, whereas community resilience showed a small inverse association (OR 0.96, 95% CI 0.93–0.99; p = 0.013). These findings underscore the importance of actionable know-how and practical access to support higher self-care categories. A trigger-based playbook linking API/PM2.5 thresholds to behaviourally specific messaging and provision of effective respirators and clean-air options warrants evaluation to strengthen population protection during seasonal haze.